EFEKTIVITAS ALKOHOL DAN CAMPURANNYA DENGAN FORMALIN SEBAGAI BAHAN PENGAWET SPESIMEN BINATANG UNTUK UDANG - Nandang Suharna; Rita Dwi Rahayu (Research Center for Biology-Indonesian Institute of Sciences, 2000)
This study was aimed at studying the effectiveness of alcohol, formaldehyde and their mixture in inhibiting fungal growth.This study contained two step. The first step was fungal isolation from specimen.One isolate was then selected to be inoculated into alcoholat various concentration (15%, 30%, 50% and 70%) with or without formaldehyde mixture.The second was fungal inoculation intoalcohol at various concentration (15%, 30%, 50%, dan 70%) with or without formaldehyde.The effectiveness of these subtances as specimen preservatives for shrimp were studied after six months incubation time.From the fisrt step, only genus group Monascus was isolated from seven specimens(Mabuia multifasciata, Myotis muricola,Chironax melanocephalus,Naya naya sputratrix, Miniopterus schreibersi blepotis,unidentified shrimp, unidentified Coelenterata).From the second step, the best growth of isolate Monascus sp.MM which isolated from the fisrt step was achieved in 70% alcohol.This fungus was not able to grow in both formaldehyde and its mixture with alcohol (1:1, 1:2, 1:3 and 1:4). The results also showed that Monascus growth was observed in alcohol with not sterilized shrimps without inoculation with Monascus sp. MM. It is recommended to apply mixture alcohol 70% with formaldehyde 1% at ratio 4:1 as animal specimen preservative to inhibit fungal growth.